PHYTOSOCIOLOGICAL STUDY OF WEED FLORA IN LOW LAND RICE ECO-SYSTEMS IN ANNAMALAI NAGAR, TAMIL NADU, INDIA - THANUNATHAN, R. KAVITHA, M. THIRUPPATHI, K. (Journal of Plant Stress Physiology)
Phytosociological study was carried out to estimate the dominant of weed flora in low land rice eco-system under varing climatic condition. The survey was conducted at Annamalai University experimental farm, Department of Agronomy, Annamalainagar during 2016 and 2017. The identified numbers were 11 and 14 during 2016 and 2017 wet season. Cyperus rotundus, Cyperus irria, Cyperus difformis, Echinocoloa colonum, Eclipta alba, Echinocoloa crusgali were the densely populated in 2016 while Cyperus rotundus, Cyperus irria, Echinocoloa colonum, Cyperus difformis, Marsilia quatrifolia, Echinocola crusgali and Bergia capensis, were the most densed in 2017. IVI computed for individual weed species in 2016 at annamalai nagar indicated that Cyperus rotundus was the predominant weed species with highest Relative abundance (RA) of 10.54 %, Relative density (RDE) of 18.97%, Relative frequency (RF) of 16% and Important value index (IVI) of 45.50 while in 2017 also obtained the Cyperus rotundus was the predominant weed species with highest Relative abundance (RA) of 10.61 %, Relative density (RDE) of 19.64%, Relative frequency (RF) of 1615.38% and Important value index (IVI) of 45.63. All other weed species were low in IVI and also rare in their occurrence with lesser frequency.